STRATEGIC ANALYSIS OF THE EXPERIENTIAL LEARNING APPROACH IN DEVELOPING YOUTH ENTREPRENEURIAL CAPABILITIES: A PERSPECTIVE ON PEDAGOGICAL INNOVATION AND CHARACTER TRANSFORMATION - Suherlan, Suherlan; Purnama, Yulian (Technopreneurship and Educational Development Review (TENDER), 2025)
This study aims to analyze the experiential learning approach as an innovative pedagogical strategy in developing youth entrepreneurial capabilities, with an emphasis on character transformation and learning innovation. Employing a literature review method with a qualitative approach and descriptive analysis, data were gathered from 30 scholarly articles and reputable sources published between 1980 and 2025, which were then rigorously filtered to 17 most relevant articles. The analysis reveals that experiential learning enhances entrepreneurial technical skills and cultivates core character values such as independence, responsibility, creativity, and resilience. This approach aligns with Kolb's Experiential Learning Theory and constructivist pedagogy, and is supported by various case studies, such as project-based entrepreneurship programs in educational institutions. Furthermore, this study reveals that systemic integration of experiential learning into curricula can serve as a strategic solution for preparing youth to be adaptive to the challenges of the digital economy and social transformation.